Guaranteeing the Protection of Citizens' Voting Rights in accordance with the Constitution in the Pancasila State in the 2024 Presidential Election - Dave Advitama; Wibowo, Basuki Rekso; Christiawan, Rio; Widjaja, Gunawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Elections as a process of changing national leadership are reflected in the 2024 presidential general election which will elect the president for the next five years. In the 2024 presidential election there will be guarantees and protection for human rights, including political rights, especially the right to vote and be elected through a process of political contestation. But in practice, there are many violations of politics, especially people's right to vote. This research aims to see to what extent the legal rules in the 2024 presidential election guarantee and protect citizens' voting rights in accordance with the constitution in the Pancasila country. This research method is literature study. The results of the research are that there are several legal regulations that protect citizens' voting rights, including Article 27 paragraph (1) of the 1945 Constitution, Article 28D paragraph (1) of the 1945 Constitution, Article 28I paragraph (2) of the 1945 Constitution, Constitutional Court Decision Number: 011-017/ PUU-I/2003, Constitutional Court Decision Number: 102/PUU-VII/2009, article 43 of Law Number 39 of 1999 concerning Human Rights (HAM) and Law Number 7 of 2017 concerning General Elections. The conclusion of the research is that existing legal regulations seek to guarantee and provide protection to citizens so that they can channel their voting rights properly as a form of channeling citizens' political rights and citizens' rights in providing strong legitimacy to the president and vice president of the Republic of Indonesia 2024-2024.